From Biopolitics to Algorithmic Governance: The Changing Nature of Power in Foucault's Power/Knowledge Framework - Kumar, Prashant (Journal of Ecohumanism, 2025)
Michel Foucault's theorisation of power/knowledge fundamentally altered the vocabulary through which political theory understands authority, subjectivity, and governance. Rejecting the classical juridical model of power as a possession exercised downward by a sovereign, Foucault described power as a relational, productive, and capillary force operating through discourse, institutions, and the body. This paper situates Foucault's framework within the wider ideological landscape of Western political thought — between liberal individualism, Marxist economism, Gramscian hegemony, and the critical theory of the Frankfurt School — before tracing its trajectory from disciplinary and biopolitical formulations to its contemporary manifestation in algorithmic governance. It argues that while the disciplinary societies Foucault described regulated bodies through enclosure, surveillance, and normalisation, and biopolitical power extended this regulation to entire populations through statistics, public health, and demography, the emergence of big data, artificial intelligence, and predictive analytics has produced a further mutation of power that this paper terms 'algorithmic governmentality.' Grounding the argument in documented cases — including the Cambridge Analytica data scandal, China's social credit system, India's Aadhaar programme, predictive policing in the United States, the Snowden revelations, and the European Union's regulatory responses under the GDPR and the AI Act — the paper identifies both the continuities between biopolitical and algorithmic power and the qualitative ruptures that distinguish them, particularly the shift from disciplining visible bodies to modulating probabilistic futures. The paper concludes that Foucault's framework, ideologically situated and empirically extended, remains indispensable for understanding contemporary digital power, even as it requires supplementation to account for the post-human, infra-individual character of algorithmic control.